Energy transition narratives in the European Union - I. L. Prokhorenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Today, there is a broad international consensus on the need to ensure carbon neutrality and, more broadly, to address global environmental issues. By promoting increasingly stringent ecological standards and climate regulations in the energy sector and consistently forcing others to emulate its example, the European Union seeks to present itself as a normative power in this area. At the same time, the EU leaders face the need to mobilize public support for the idea of the sustainable climate-oriented transition in order to mitigate its negative economic and social effects. This, in turn, requires the construction and promotion of the compelling and unambiguous energy transition narrative designed to legitimize the EU’s environmental and energy policy. This paper identifies and examines the key elements of such a narrative propagated within the European Union, as well as assesses its perception by various groups of the European countries’ population. The author also outlines a few alternative ‘greentransition’ narratives, which have arisen as a reaction to both the deficiencies of the EU’s energy policy and the challenges posed by the Ukrainian crisis. The author concludes that the EU leaders and the non-governmental and non-profit actors backing them have managed to build a broad and solid public consensus around the official narrative of the energy transition. Under these conditions, one of the central objectives facing the EU leaders is to maintain and strengthen the attained level of public support for its policies, given new transition-related challenges to the territorial integrity and political cohesion of the union. The latter include high inflation rates and the general rise in the cost of living, negative tendencies in the labor market due to its structural transformation, as well as the growing economic heterogeneity of the member states.